Konseling Pastoral dengan Teknik Cognitive Restructuring pada Pelayan Khusus - Molle, Jhonderic; Brek, Yohan (PT. Giat Konseling Nusantara, 2025)
Specialized waiters often face emotional and mental stress that can interfere with their health and the quality of service. Using cognitive restructuring techniques, this counseling aims to help the maids recognize and change their negative mindsets. Through the process of identifying, evaluating, and replacing negative thoughts with positive thoughts, servants are expected to improve their mental well-being. This study uses a qualitative method with in-depth interviews to explore the experience of servants in counseling. The results showed that this technique was effective in reducing stress and increasing the confidence of the servants, which in turn had a positive impact on their service to the congregation. These findings highlight the importance of counseling support for special caregivers in maintaining their mental and spiritual health.